Infusing 21st Century Skill Development into the Undergraduate Curriculum: The Formation of the iBEARS Network - Alex T. St. Louis (American Society for Microbiology, 2021)
ABSTRACT The demonstrated gap between skills needed and skills learned within a college education places both undergraduates seeking gainful employment and the employers seeking highly skilled workers at a disadvantage. Recent and up-and-coming college graduates should possess 21st century skills (i.e., communication, collaboration, problem solving), skills that employers deem necessary for the workplace. Research shows that the development of this skillset can help narrow the gap in producing highly skilled graduates for the science, technology, engineering, and mathematics (STEM) workforce. We propose the development of 21st century skills by utilizing the project-based learning (PjBL) framework and creating the inclusive biologist exploring active research with students (iBEARS) program, allowing undergraduate students to hone their 21st century skills and prepare for transition and success within the workplace.